Intelligent Design and Imaginary Worlds in Cost-Effectiveness Claims: An Overview of Commentaries in INNOVATIONS in Pharmacy from July 2016 to February 2017 - Paul C Langley (University of Minnesota Libraries Publishing, 2017)
Over the past 30 years, thousands of modeled cost-effectiveness studies have been published. Whether this effort has been worthwhile is debatable. For supporters of modeled cost-effectiveness studies, this effort has been worthwhile because the modeled claims are intended to inform health care decision makes. To opponents, the effort is seen as largely a waste of time because the claims are typically non-evaluable. Rather than subscribing to the standards of normal science in its focus on hypothesis testing through experimentation and replication, opponents have viewed practitioners in health technology assessment as being content to develop imaginary worlds with no thought to their role in practical decision-making. Given this ongoing commitment to constructing imaginary worlds, the purpose of this commentary is bring together the various commentaries, together with supporting publications that have appeared in INNOVATIONS in Pharmacy since mid-2016. This is in response to requests from faculty and graduate students at the College of Pharmacy, University of Minnesota for an overview of the arguments presented to date in support of a new research program that rejects imaginary constructs in favor of credible, evaluable and replicable claims to support formulary decision making.   Type: Commentary